Estetika Simbolik pada Desain Bangunan Komersil di Kawasan Perdagangan Cihampelas - Doni Morika (Humaniora, 2012)
The notion of aesthetics so far did not produce a conclusion crystallized from various points of view offered by observer. It came from the standpoint of behavioral and psychological environment to obtain the aesthetic sense which was based on the notion of meaning, perception, and aesthetic experience. In the philosophy of beauty "aesthetic experience" was in the view of phenomenology of the aesthetic experience of the "thing". Sensory aesthetic experience was based on observations at the same time with the whole soul of the human body and produced a feeling of participating bound, carried away, and enticed her feelings toward an aesthetic pleasure and experience. The question raised then is how these symptoms that could affect the behavior settings in the broad sense. Good answers to these questions will be able to make designers better understand the behavior of the users as well as empower designers to contribute to the environment.